Biomimetic enterobactin analogue mediates iron-uptake and cargo transport into E. coli and P. aeruginosa. Issue 30 (21st June 2021) - Zscherp, Robert; Coetzee, Janetta; Vornweg, Johannes; Grunenberg, Jörg; Herrmann, Jennifer; Müller, Rolf; Klahn, Philipp
Abstract : The design, synthesis and evaluation of the enterobactin derivative (AcO)EntKL is reported, which mediates iron uptake and cargo transport into E. coli and P. aeruginosa and was able to compete with human enterobactin and iron binding proteins. Abstract : The design, synthesis and biological evaluation of the artificial enterobactin analogue EntKL and several fluorophore-conjugates thereof are described. EntKL provides an attachment point for cargos such as fluorophores or antimicrobial payloads. Corresponding conjugates are recognized by outer membrane siderophore receptors of Gram-negative pathogens and retain the natural hydrolyzability of the tris-lactone backbone. Initial density-functional theory (DFT) calculations of the free energies of solvation (Δ G (sol)) and relaxed Fe–O force constants of the corresponding [Fe-EntKL ] 3− complexes indicated a similar iron binding constant compared to natural enterobactin (Ent ). The synthesis of EntKL was achieved via an iterative assembly based on a 3-hydroxylysine building block over 14 steps with an overall yield of 3%. A series of growth recovery assays under iron-limiting conditions with Escherichia coli and Pseudomonas aeruginosa mutant strains that are defective in natural siderophore synthesis revealed a potent concentration-dependent growth promoting effect of EntKL similar to natural Ent . Additionally, four cargo-conjugates differing in molecular size were able to restore growth of E. coli indicating an uptake into the cytosol. P. aeruginosa displayed a stronger uptake promiscuity as six different cargo-conjugates were found to restore growth under iron-limiting conditions. Imaging studies utilizing BODIPYFL -conjugates, demonstrated the ability of EntKL to overcome the Gram-negative outer membrane permeability barrier and thus deliver molecular cargos via the bacterial iron transport machinery of E. coli and P. aeruginosa .